Constructivism, Identity, and Discourse in Terrorism - Tulga, Ahmet Yigitalp (Universitas Brawijaya, 2022)
Terrorism is a phenomenon with a long history. Scholars from many different disciplines research terrorism. One of the disciplines studying the phenomenon of terrorism is International Relations. Significantly after the 9/11 terrorist attacks, the discipline's interest in terrorism increased dramatically. However, increasing academic studies since the early 2000s did not lead to an increase in the contribution of the field to Terrorism Studies. The state-centric perspective of Neorealism and Neoliberalism is a fundamental reason behind this problem. Constructivism offers an alternative to the state-centric view. In this context, I examine the role of identity and discourse on terrorism by adopting the Constructivist perspective. Within this scope, the manifestos of eight different terrorists within three various terrorist organizations were examined. In parallel, news about the terrorists whose manifestos were examined was analyzed. Using text analysis, results suggest that both terrorists and the media divide the world into two